Data from 'Graphic Medicine' as a Mental Health Information Resource: Insights from Comics Producers. (30th August 2016) - Farthing, Anthony; Priego, Ernesto
This dataset contains the full text transcripts from 15 semi-structured interviews (approximately 44, 100 words) conducted during November and December 2014 with participants involved in various aspects of the process of health-related comics production. These participants are authors and publishers and their work is publicly recognised in the comics community. The dataset has been deposited in the Open Health Data Dataverse repository as a zipped folder containing 15 individual simple text files corresponding to each interview and a ReadMe file containing contextual information and other metadata. An initial domain analysis of the interviews was published as Farthing, A., & Priego, E. (2016). 'Graphic Medicine' as a Mental Health Information Resource: Insights from Comics Producers. The Comics Grid: Journal of Comics Scholarship, 6(1), 3. DOI:http://doi.org/10.16995/cg.74